1999
DOI: 10.1111/j.1749-6632.1999.tb07687.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Matrix Metalloproteinases and Tissue Inhibitors of Metalloproteinases in Blood and Tissues: Clinical and Experimental Applications

Abstract: The balance between production and activation of MMPs and their inhibition by TIMPs is a crucial aspect of cancer invasion and metastasis. On the basis of the concept that MMPs synthesized in tissues seep into the bloodstream, we have examined MMP levels in the plasma of patients with cancer. In colorectal, breast, prostate, and bladder cancer, most patients with aggressive disease have increased plasma levels of gelatinase B. In patients with advanced colorectal cancer, high levels of either gelatinase B or T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(142 citation statements)
references
References 65 publications
4
131
0
7
Order By: Relevance
“…Analysis of both primary and metastatic tumors has shown increased relative MMP expression at the metastatic site, supporting a role in tumor migration and spread (44). Additionally, increased MMP levels have been reported in the plasma and urine of patients with a variety of advanced malignancies (45). Cancer outcome studies have also shown that increased expression of MMPs is associated with shortened patient survival (10,12,46).…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of both primary and metastatic tumors has shown increased relative MMP expression at the metastatic site, supporting a role in tumor migration and spread (44). Additionally, increased MMP levels have been reported in the plasma and urine of patients with a variety of advanced malignancies (45). Cancer outcome studies have also shown that increased expression of MMPs is associated with shortened patient survival (10,12,46).…”
Section: Discussionmentioning
confidence: 95%
“…Zucker et al 29 demonstrated that the high expression of MMPs, observed mainly in cancerous processes, is due to changes in gene transcription, with the increase of these enzymes leading to a poor prognosis for various types of cancer. 30,31 A study conducted by Benson et al 32 evaluated the expression of MMPs in different types of tissues with breast cancer and normal tissues.…”
Section: Zinc and Metalloproteinases Of The Extracellular Matrixmentioning
confidence: 99%
“…The protease species as well as their levels would be relatively easy to determine by the analysis of biopsy materials from individual patients by conventional immunohistochemistry, ELISA and other assay methods. [39][40][41][42] Once they are determined, it would also be easy to generate appropriate protease activation mutants of SeV and related envelope viruses. The safety of recombinant SeVs is another key issue.…”
Section: Mmp-dependent Cellmentioning
confidence: 99%